RESPON TANAMAN LADA PERDU TERHADAP PEMUPUKAN NPK PADA JENIS TANAH INCEPTISOLS DAN ULTISOLS - Agus Ruhnayat (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Response of bushy black pepper to NPK fertilizers on inceptisols and ultisols soilsBlack pepper could be developed in the form of bushy pepper. Many of black pepper cultivating areas in Indonesia are on Inceptisols and Ultisols soil types such as in Lampung, Bangka and Borneo. Each type of soil has different physical, che-mical and biological characteristics, so that the level of their input needs will also vary. In general, the level of Inceptisols and Ultisol soil fertility is relatively low. Fertilizer application is needed to increase its fertility. The study was conducted in Indonesian of Medicinal and Aromatic Crops Research Institute (IMACRI) Bogor using plastic pots under the auspices of paranet (light intensity 75%) from January 2000 to December 2002. The research aims to study the response of bushy black pepper to NPK fertilization on Inceptisols and Ultisols soil, in order to obtain the dosage and composition of the proper nutrients to promote growth and production. The research was arranged in split plot design, repeated 3 times. As the main plot are two types of soil (Inceptisols and Ultisols), sub plots are combination of dosages and composition of NPK nutrients, namely : 20 (1:1:1), 40 (1:1:1), 60 (1:1: 1), 80 (1:1:1), 20 (1:1:2), 40 (1:1:2), 60 (1:1:2), and 80 (1:1:2) g/plant. The ob-served parameters were number of leaves, number of secondary branches, number of panicles and fruit weight. The results sho-wed, bushy black pepper gives a signify-cantly different response to NPK fertiliza-tion planted on Inceptisols and Ultisols soils. The best growth and production of bushy black pepper grown on Inceptisol soil obtained by NPK fertilizer (1:1:1) 20-60 g/plant, while on Ultisols soil at NPK fertilizer (1:1:2) 40-120 g/plant. Bushy black pepper grown on Inceptisols soil produce an average fresh weight of pepper berry 7.09-11.63% higher than the one planted on Ultisols soil.